Once-weekly bortezomib had similar effectiveness and lower thrombocytopenia occurrence compared with twice-weekly bortezomib regimen in treating patients with newly diagnosed multiple myeloma in China. Issue 39 (September 2019) - Yao, Rongxin; Hu, Xudong; Zhou, Shuping; Zhang, Qianying; Huang, He; Sun, Ni; Guo, Wenjian; Yu, Kang; Lin, Ying
Abstract : Abstract: The study aims to examine the treatment effect and adverse reactions of patients with newly diagnosed MM receiving different bortezomib-based regimens. This was a retrospective study of patients with newly diagnosed MM and who were treated with bortezomib-based combined chemotherapy at the Department of Hematology of the 2 affiliated hospitals of Wenzhou Medical University between July 2009 and May 2016. Cox proportion hazard multivariate analyses were carried out to assess the differences in treatment effect and adverse events between standard (1.3 mg/m 2 on days 1, 4, 8, 11) and weekly (1.6 mg/m 2 on days 1, 8, 15) cohorts, as well as the differences between intravenous injection and subcutaneous injection therapy. Progression-free survival (PFS) and overall survival (OS) were assessed using Kaplan–Meier method and the log-rank test. Among the 117 patients, 78 patients were treated with bortezomib standard therapy and 39 patients were treated with bortezomib weekly therapy (all with intravenous injection). In all patients, the treatment strategy was not independently associated with PFS or OS. The patients in the weekly therapy group had less thrombocytopenia events than those in the standard therapy group. The subcutaneous route had similar treatment effect as the intravenous route, but the incidence of peripheral neuropathy was lower. The once-weekly bortezomib regimen was similar in effectiveness to standard therapy in treating patients with newly diagnosed MM, but the incidence of thrombocytopenia was lower with the weekly regimen compared with the standard regimen.